2015
DOI: 10.2514/1.b35638
|View full text |Cite
|
Sign up to set email alerts
|

Physical Insight into Fuel/Air Mixing with Hypermixer Injectors for Scramjet Engines

Abstract: Ecient mixing of fuel and air is a major objective for the successful operation of scramjet engines, where the supersonic combustion process must occur within an extremely short time frame in the hypersonic ight. This paper presents the insights gained into the key design factors and underlying mechanism for fuel/air mixing enhancement with streamwise vortices introduced by alternating wedges called hypermixers. The results of a parametric numerical study and sensitivity analysis suggest that: Narrow spanwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 20 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The numerical investigation of the hyper mixer with a row of alternating wedges having central fuel injection as shown in fig. 2 (Ogawa and Kodera 2015) shows the favorable efficient fuel/air mixing in narrow spanwise spacing which creates strong streamwise vortex but does not improve the fuel/air mixing.…”
Section: Review Of Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…The numerical investigation of the hyper mixer with a row of alternating wedges having central fuel injection as shown in fig. 2 (Ogawa and Kodera 2015) shows the favorable efficient fuel/air mixing in narrow spanwise spacing which creates strong streamwise vortex but does not improve the fuel/air mixing.…”
Section: Review Of Literaturementioning
confidence: 98%
“…The higher fuel/air mixing is achieved by greater vertical height and augments streamwise vortex circulation with the help of steeper ramp angle (Ogawa and Kodera 2015). The streamwise vortex interaction across the symmetry plans plays a vital role in convective mixing of fuel air.…”
Section: Fig 5: the Schematic Of Cavity Shaped Combustormentioning
confidence: 99%
“…For supersonic combustion, typical solutions for mixing intensification are based on vorticity generation such as by struts (hypermixers), cavities, shock wave impinging the fuel jet, etc. [117][118][119][120]. Plasma-based mixing is still considered an exotic approach.…”
Section: Mixing Enhancement By Electric Dischargesmentioning
confidence: 99%
“…It was found that the alternating wedge strut gives better mixing and robust turbulent structures inducing streamwise vortices. The numerical study with alternating wedge strut was conducted by Ogawa and Kodera (2015). The authors conducted a parametric study of the alternating wedge strut by varying the ramp angle of the trailing wedge and the width of the wedge.…”
Section: Introductionmentioning
confidence: 99%